PERSPECTIVES ON FAMILY FIRMS IN THE ROMANIAN ECONOMIC FRAMEWORK - Viorel CORNESCU; Andreea STROE (Challenges of the Knowledge Society, 2018)
The paperwork focuses on emphasizing the increasingly significant role of family firms in the Romanian economic framework, by bringing into attention legislative matters, their advantages and disadvantages compared to other similar forms of organization (sole proprietorship (IF) and PFA (self-employed person)). The importance of FFs is indisputable, not only generally, from the economic point of view, but also in terms of the commitment shown to local communities, business responsibility, long-term stability and moral values. They are also a fertile soil for entrepreneurship as incubators for future entrepreneurs. Our goal is to capture their features, their evolution in time in the local framework, development tendencies, but also the peculiarities of their financial instrumentation. Their specific aspects in what concerns financial instrumentation of FFs may be the subject of future debates on proposals to improve the management of their work, to analyze their financial activity by highlighting the legislative aspects which are compared to similar forms of organization, by also assessing the evolution in time of family firms in terms of their importance within the economy. Therefore, the paperwork points out some of the key aspects and characteristics of such organizations which act as a balance in entrepreneurial development, along with the economic support of thousands of families, both from rural and urban environment.